CB1 receptor neutral antagonist treatment epigenetically increases neuropeptide Y expression and decreases alcohol drinking. (1st September 2021) - Dulman, Russell S.; Zhang, Huaibo; Banerjee, Ritabrata; Krishnan, Harish R.; Dong, Bin; Hungund, Basalingappa L.; Vinod, K. Yaragudri; Pandey, Subhash C.
Abstract: Alcohol consumption is mediated by several important neuromodulatory systems, including the endocannabinoid and neuropeptide Y (NPY) systems in the limbic brain circuitry. However, molecular mechanisms through which cannabinoid-1 (CB1) receptors regulate alcohol consumption are still unclear. Here, we investigated the role of the CB1 receptor-mediated downstream regulation of NPY via epigenetic mechanisms in the amygdala. Alcohol drinking behavior was measured in adult male C57BL/6J mice treated with a CB1 receptor neutral antagonist AM4113 using a two-bottle choice paradigm while anxiety-like behavior was assessed in the light-dark box (LDB) test. The CB1 receptor-mediated changes in the protein levels of phosphorylated cAMP-responsive element binding protein (pCREB), CREB binding protein (CBP), H3K9ac, H3K14ac and NPY, and the mRNA levels of Creb1, Cbp, and Npy were measured in amygdaloid brain structures. Npy -specific changes in the levels of acetylated histone (H3K9/14ac) and CBP in the amygdala were also measured. We found that the pharmacological blockade of CB1 receptors with AM4113 reduced alcohol consumption and, in an ethanol-naïve cohort, reduced anxiety-like behavior in the LDB test. Treatment with AM4113 also increased the mRNA levels of Creb1 and Cbp in the amygdala as well as the protein levels of pCREB, CBP, H3K9ac and H3K14ac in the central and medial nucleus of amygdala, but not in the basolateral amygdala. Additionally, AM4113 treatment increased occupancy of CBP and H3K9/14ac at the Npy gene promoter, leading to an increase in both mRNA and protein levels of NPY in the amygdala. These novel findings suggest that CB1 receptor-mediated CREB signaling plays an important role in the modulation of NPY function through an epigenetic mechanism and further support the potential use of CB1 receptor neutral antagonists for the treatment of alcohol use disorder. Highlights: CB1 receptor neutral antagonist decreases alcohol drinking and anxiety-like behavior. CB1 receptor blockade increases CREB and CBP mRNA and protein levels in the amygdala. CB1 receptor blockade causes chromatin remodeling by increasing histone H3K9 and H3K14 acetylation in the amygdala. Increased CBP and histone acetylation at  Npy  promoter following CB1 receptor blockade is associated with increases in NPY.